Crystallization process systems - Jones, A. G. (Alan G.) (Oxford ; Boston : Butterworth-Heinemann, 2002)
Crystallization Process Systems gives a clear, concise, balanced and up to date presentation of crystallization and solid-liquid separation of the crystalline product. The information is presented in a coherent, concise and logical sequence based on the fundamentals of particulate crystallization processes as systems. By emphasising the analysis, design and operation of particulate crystallization processes as systems, the reader will be able to make a better judgement about the best, cheapest and most effective production method to use. Crystallization Process Systems gives a wider view and an overview of the subject of crystallization as a whole. It provides an ideal lead-in to more specialized works such as Crystallization and Solid-Liquid Separation - also published by BH. Presents a coherent, concise and logical sequence based on the fundamentals of particulate crystallization processes as systemsEmphasis on the design and optimization of the crystallization processing system.
Particulate Crystal Characteristics; Fluid-particle Transport Processes; Crystallization Principles and Techniques; Crystal Formation Processes; Crystallizer Design and Operation; Solid-Liquid Separation Processes; Design of Crystallization Process Systems.
Includes bibliographical references (p. [299]-328) and indexes.
Keywords: Crystallization; Crystallization -- Industrial applications; Electronic books